1950°C Post Implantation Annealing of Al+ Implanted 4H-SiC: Relevance of the Annealing Time. (12th August 2016) - Fedeli, P.; Gorni, M.; Carnera, A.; Parisini, A.; Alfieri, G.; Grossner, U.; Nipoti, R.
Abstract : Previous studies have shown that the electrical activation of a given implanted Al concentration in 4H-SiC increases with the increasing of the post implantation annealing temperature up to 1950–2100°C and different annealing times in the range 0.5–5 min. This study shows that, at 1950°C, the electrical activation of Al implanted in 4H-SiC increases with the increase of the annealing time up to attain saturation for annealing times longer than 22 min. Samples were obtained from the same Al implanted HPSI 4H-SiC wafer with an implanted Al concentration lower than the Al solubility limit in 4H-SiC at the annealing temperature of 1950°C. The annealing time was varied in the range 5–40 min.